Clickbait: AEC792/WC453, 3/2024 - Patten, Nicole; Telg, Ricky; Kent, Kevin (EDIS, 2024)
This publication provides an overview of clickbait and its characteristics. The publication also discusses a few implications of clickbait use. Written by Nicole Patten, Ricky Telg, and Kevin Kent, and published by the UF/IFAS Department of Agricultural Education and Communication, March 2024.